2022
DOI: 10.1186/s40001-022-00716-w
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of resistant chronic migraine with anti-CGRP monoclonal antibodies: a systematic review

Abstract: Background Resistant chronic migraine is a highly disabling condition which is very difficult to treat. The majority of the treatments for migraine prophylaxis are nonspecific and present weak safety profiles, leading to low adherence and discontinuation. Currently, monoclonal antibodies (mAb) targeting the trigeminal sensory neuropeptide, calcitonin gene-related peptide (CGRP), are available for migraine prophylaxis being the first drugs developed specifically to target migraine pathogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 97 publications
0
15
0
1
Order By: Relevance
“…A systematic review which was conducted to evaluate the treatment of resistant chronic migraine with anti-CGRP monoclonal antibodies mentions that developing tachyphylaxis is possible. This could be due to an increased development of antibodies in response to treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review which was conducted to evaluate the treatment of resistant chronic migraine with anti-CGRP monoclonal antibodies mentions that developing tachyphylaxis is possible. This could be due to an increased development of antibodies in response to treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, with the advent of new data on drug therapy in migraine, this era is also witnessing a remarkable change in its management[ 41 ]. Recent studies have shown mechanism-based therapies like anti-calcitonin gene-related peptide monoclonal antibodies (erenumab, tinezumab, fremanezumab and galcanezumabas) as promising drugs in the preventive management of migraine[ 13 , 42 ]. In addition to rapid onset, these drugs also carry fewer adverse effects (mainly injection site reactions).…”
Section: Discussionmentioning
confidence: 99%
“…The development and use of monoclonal antibodies directed against the neuropeptide CGRP or its receptor are the most recent achievement in the field of migraine [ 287 ]. However, despite the success displayed by such monoclonal antibodies, there is still a great percentage of migraine patients for whom the beneficial effects are minimal or completely absent, which underscores the involvement of other biological players in migraine generation and maintenance besides CGRP [ 288 , 289 , 290 ]. An important role is played by NO.…”
Section: Fitting Together the Pieces Of A Complex Picturementioning
confidence: 99%